Amino-Oligosaccharide as a Plant Immune Inducer to Manage Stem Canker Disease Caused by Neoscytalidium dimidiatum in Dragon Fruit (Hylocereus spp.) - Xueying Shang; Qing Tan; Ziqin Bai; Jieyu Li; Geng Liu; Chenlan Li; Hui Luo (Journal of Chemistry)
The dragon fruit (Hylocereus spp.) industry is often impacted by plant diseases, especially the stem canker disease caused by Neoscytalidium dimidiatum. The present study demonstrated that a 5% amino-oligosaccharide solution exhibited a lower in vitro antifungal activity (19.60%) against N. dimidiatum, while displaying significant in vivo efficacy (83.80%) in controlling stem canker disease in dragon fruit during field trials. Meanwhile, we found that, compared to the control, amino-oligosaccharide significantly augmented the total phenolic, lignin, and flavonoid contents as well as effectively enhanced the activities of antioxidant enzymes in dragon fruit. Furthermore, the nontargeted metabolomics analysis revealed that amino-oligosaccharide treatment significantly impacted flavonoids content and predominantly influenced key Kyoto Encyclopedia of Genes and Genomes (KEGG) pathways associated with starch and sucrose metabolism (ko00500), proximal tubule bicarbonate reclamation (ko04964), glutamatergic synapse (ko04724), glutathione metabolism (ko00480), and protein digestion and absorption (ko04974) in dragon fruit. These findings underscore the substantial potential of amino-oligosaccharide as a plant immune inducer in effectively suppressing stem canker disease on dragon fruit.